The Atrium in Atrial Fibrillation – A Clinical Review on How to Manage Atrial Fibrotic Substrates - Cunha, Pedro Silva; Laranjo, Sérgio; Heijman, Jordi; Oliveira, Mário Martins (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is the most common sustained arrhythmia in the population and is associated with an important clinical and economic burden. Rigorous assessment of the presence and degree of an atrial arrhythmic substrate is important for determining treatment options, for predicting long-term success after catheter ablation, and as a substrate critical in the pathophysiology of atrial thrombogenesis. Catheter ablation of AF has developed into an important rhythm-control strategy and nowadays is one of the most common cardiac ablation procedures performed worldwide, with its success inversely related to the extent of atrial structural disease. Although atrial substrate evaluation remains complex, several diagnostic resources allow for a more comprehensive assessment and quantification of the extent of left atrial structural remodelling and the presence of atrial fibrosis. In this review, we summarize the current knowledge on the pathophysiology, aetiology and electrophysiological aspects of atrial substrates promoting the development of AF. We also describe the risk factors for its development and how to diagnose its presence using imaging, the electrocardiogram and by electroanatomic voltage mapping. Finally, we discuss recent data regarding fibrosis biomarkers that could help in the diagnosis of atrial fibrotic substrates.